1987
DOI: 10.1128/jb.169.7.3035-3043.1987
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid concentrations in Rhodospirillum rubrum during expression and switch-off of nitrogenase activity

Abstract: The amino acid concentrations in the phototrophic bacterium Rhodospirillum rubrum were measured during growth under nif-repressing and nif-derepressing conditions. The effects of ammonium, glutamine, darkness, phenazine methosulfate, and the inhibitors methionine sulfoximine and azaserine on amino acid levels of cells were tested. The changes were compared to changes in whole-cell nitrogenase activity and ADP-ribosylation of dinitrogenase reductase. Glutamate was the dominant amino acid under every growth cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 44 publications
4
40
1
Order By: Relevance
“…These results indicate that glutamine is not the signal for the darkness response. Consistent with this, a rapid and drastic increase in the glutamine pool has been seen after addition of NH z 4 , but only a very small change was seen after the darkness shift in R. rubrum (Kanemoto & Ludden, 1987;Li et al, 1987). These data suggest that the modification of GS and the regulation of nitrogenase activity are two independent events, and both are regulated by P II in response to NH z 4 and darkness stimuli.…”
Section: Effects Of Darkness Do Not Seem To Be Mediated Through Glutasupporting
confidence: 71%
“…These results indicate that glutamine is not the signal for the darkness response. Consistent with this, a rapid and drastic increase in the glutamine pool has been seen after addition of NH z 4 , but only a very small change was seen after the darkness shift in R. rubrum (Kanemoto & Ludden, 1987;Li et al, 1987). These data suggest that the modification of GS and the regulation of nitrogenase activity are two independent events, and both are regulated by P II in response to NH z 4 and darkness stimuli.…”
Section: Effects Of Darkness Do Not Seem To Be Mediated Through Glutasupporting
confidence: 71%
“…NH 4 Ď© itself is not the direct signal for the DRAT-DRAG system, as L-methionine-D-sulfoximine, an inhibitor of GS, can significantly block the NH 4 Ď© effect on nitrogenase activity in both A. brasilense (12) and R. rubrum (14). Consistent with this, the intracellular glutamine concentration increases rapidly after NH 4 Ď© treatments in both R. rubrum and A. brasilense (11,15,18). GS activity is reduced in the A. brasilense ntrBC mutants (40), and the products of ntrBC regulate GS synthesis in other nitrogen-fixing bacteria, such as K. pneumoniae (6), Rhizobium meliloti (4,34), and B. japonicum (22).…”
Section: Fig 3 Regulation Of Nitrogenase Activity By Nhsupporting
confidence: 56%
“…The in vitro studies performed with GlnD from R. rubrum (6) and Escherichia coli (4,5) indicate that glutamine is the main signal inducing GlnD deuridylylating activity. In fact, it has been shown that in glutamate-grown cells, there is a small increase in the glutamine concentration upon transfer to darkness (8). This observation might explain the observed P II protein deuridylylation upon exposure to darkness in glutamate-grown cells.…”
mentioning
confidence: 61%